El arte y la guerra. La movilización cultural y artística en torno del Fondo Patriótico Malvinas Argentinas en la ciudad de Córdoba - Maria Verónica Basile; Yanina Floridia (Nuevo mundo - Mundos Nuevos, 2019)
Since mid-April to May a mass of adhesions and demonstrations were display to support the “recovery” of national sovereignty over the Malvinas Islands. A variety of events were folded to the "cause", collecting money and other goods to donate them to Patriotic Fund Malvinas Argentinas or deliver to the Third Army Corps. In those moments, solidary accompaniment to soldiers was the objective why society was mobilized. In the following lines we proposed to review and analyze social and cultural actions that emerged around war in the city of Córdoba. A first hypothesis considers that from different spaces, actions were multiplied. Although it had fundraising destiny, they contributed to reconstruct social networks that had been eliminated, sabotaged or controlled by the dictatorial government. The initiative to raise funds for the soldiers promoted various artistic, cultural and social institutions and brought together together people from different social background. We focus on the civil sphere, inquiring about the organizers, the activities and the different meanings that were articulated around these artistic - cultural actions during the days that the conflict lasted.